Islamic Religious Education Teacher’s Problems in Implementing the Independent Curriculum in Junior High School Number 1 Suralaga - Julaen; Deddy Ramdhani (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims: 1) To find out the problems faced by Islamic religious education teachers in implementing an independent curriculum. 2) To find out the solutions that schools do to overcome these problems. This research uses qualitative methods. The subject in this research is the Islamic religious education teachers. Data collection techniques using observation, interviews, and documentation techniques. The data analysis technique used source triangulation and technique triangulation. The research findings show that there are several problems faced by Islamic education teachers in implementing an independent curriculum, which can be summarized as follows: (1) Lack of deep understanding of the concepts and objectives of the independent curriculum. (2) lack of understanding in making teaching modules. (3) lack of socialization of the application of the independent curriculum. (4) Difficulty in making teaching modules.